Recent Advances in Hydro- and Biohydrometallurgy - Komnitsas, Kostas A. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Minerals presents recent, select studies that highlight advances in the fields of hydro- and biohydrometallurgy. It aims to attract the interest of readers and especially of young scientists and students in this fascinating scientific discipline.